Organizational change - strategy and complexity - MacKechnie, G. (Economic & Social Studies, 1976)
Research on organisational change has rarely treated the nature of the change as a variable. This can be done by differentiating changes in terms of complexity. By treating both change complexity and change strategy as variables a more elaborate model of the change process can be established, forming a link between the study of change and other branches of organisation theory.
Keywords: Economics; Sociology